ПИТАННЯ ПОМІСНОЇ УКРАЇНСЬКОЇ ЦЕРКВИ У МАТЕРІАЛАХ ПЕРІОДИКИ УКРАЇНСЬКОЇ ДІАСПОРИ США ЯК ОДИН ІЗ ЧИННИКІВ НАЦІОНАЛЬНОЇ САМОІДЕНТИФІКАЦІЇ - Біловус, Леся Іванівна (My University, 2017)
Стаття розглядає українську періодику США як традиційного презентатора питання створення Єдиної Помісної української церкви, дискусійний майданчик для представників різних позицій. Проаналізовані публікації свідчать про те, що статус Помісності сприятиме вирішенню як становища українських релігійних громад за океаном, так і сприятиме збереженню національної ідентичності закордонних українців. Матеріали україномовної діаспорної періодики США свідчать про те, що сьогодні в Україні та діаспорі поступово зростає запит на національну Церкву, яка могла б об’єднати суспільство, оскільки роз’єднаність українських церков дискредитує імідж України в світі, є постійним джерелом суспільної напруги, становить потенційну загрозу національній безпеці України. Тому створення Української Помісної Церкви також відповідає й інтересам національної безпеки України. In the article Ukrainian periodicals of the USA are treated as a traditional platform of different points of view about establishing of the Ukrainian Unified Independent Church. The analysed articles prove that Unified Independency will improve the status of Ukrainian religious communities over the ocean as well as save the national identity of foreign Ukrainians. Nowadays published materials of Ukrainian diaspora highlight the increasing interest to the National Church in Ukraine and abroad. The author of the research suggests that the National Church can unite the society taking to the consideration the fact that separation of Ukrainian churches discredits the image of Ukraine in the world, causes strong social tension and can harm the national security of Ukraine. That is why the establishing of Ukrainian Unified Independent Church meets the interests of national security of Ukraine.
MATTER OF UKRAINIAN UNIFIED INDEPENDENT CHURCH IN UKRAINIAN DIASPORA’S PERIODICALS OF THE USA AS THE FACTOR OF NATIONAL SELF-IDENTITY
Keywords: Національна ідентичність, українська діаспора США, українська церква, україномовна періодика; Ukrainian Unified Independent Church, national identity, Ukrainian diaspora of the USA, Ukrainian periodicals